2008
DOI: 10.1103/physrevd.78.024037
|View full text |Cite
|
Sign up to set email alerts
|

Flat rotation curves in Chern-Simons modified gravity

Abstract: We investigate the spacetime of a slowly rotating black hole in the Chern-Simons modified gravity. The long range feature of frame-dragging effect under the Chern-Simon gravity well explains the flat rotation curves of galaxies which is a central evidence of dark matter. Our solution provides a different scenario of rotating space from Gödel's solution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
(25 reference statements)
0
50
0
Order By: Relevance
“…In particular, it was found that the CS modified theory predicts an anomalous precession effect [14], which was tested [15] with LAGEOS [16]. Another constraint on the non-dynamical theory was proposed in [17], where it was considered that the CS correction could be used to explain the flat rotation curves of galaxies. However, in [18] a bound was placed on the non-dynamical model with a canonical CS scalar that is eleven orders of magnitude stronger than the Solar System one, using double binary pulsar data.…”
mentioning
confidence: 99%
“…In particular, it was found that the CS modified theory predicts an anomalous precession effect [14], which was tested [15] with LAGEOS [16]. Another constraint on the non-dynamical theory was proposed in [17], where it was considered that the CS correction could be used to explain the flat rotation curves of galaxies. However, in [18] a bound was placed on the non-dynamical model with a canonical CS scalar that is eleven orders of magnitude stronger than the Solar System one, using double binary pulsar data.…”
mentioning
confidence: 99%
“…Despite these drawbacks, the Alexander-Yunes far field solution and the KMT slow rotating solution are useful for understanding the CS effects on physical observables. KMAT [33] showed that their solution remarkably explains galactic flat rotation curves without the need to invoke hypothetical dark matter. They also calculated the effect of frame dragging on spin precession, which could provide a way to observationally test CS gravity.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we shall consider the KMT solution [33,34] to study the effects of CS modified gravity on the phase shift in neutron interferometry using, in addition, the equations of optical-mechanical analogy for rotating sources [36]. The final formula for phase shift shows a combination of different effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent this difficulty, in [5,9], the concept of the dynamical Chern-Simons coefficient was introduced. Within this formulation, where the function θ multiplying the topological * RR term in the modified gravity action is considered as a dynamical variable, it was shown that the Kerr metric must be adequately modified to satisfy the new modified equations of motion involving dynamics of θ as well [10]. Therefore, a natural problem emerges -whether other known metrics, or, probably, other parameters of the theory must suffer any modification to solve the modified equations of motion?…”
mentioning
confidence: 99%